The distribution and degradation of radiolabeled superparamagnetic iron oxide nanoparticles and quantum dots in mice - Bargheer, Denise; Giemsa, Artur; Freund, Barbara; Heine, Markus; Waurisch, Christian; Stachowski, Gordon M.; Hickey, Stephen G.; Eychmüller, Alexander; Heeren, Jörg; Nielsen, Peter (Beilstein Journal of Nanotechnology, 2015)
51Cr-labeled, superparamagnetic, iron oxide nanoparticles (51Cr-SPIOs) and 65Zn-labeled CdSe/CdS/ZnS-quantum dots (65Zn-Qdots) were prepared using an easy, on demand, exchange-labeling technique and their particokinetic parameters were studied in mice after intravenous injection. The results indicate that the application of these heterologous isotopes can be used to successfully mark the nanoparticles during initial distribution and organ uptake, although the 65Zn-label appeared not to be fully stable. As the degradation of the nanoparticles takes place, the individual transport mechanisms for the different isotopes must be carefully taken into account. Although this variation in transport paths can bring new insights with regard to the respective trace element homeostasis, it can also limit the relevance of such trace material-based approaches in nanobioscience. By monitoring 51Cr-SPIOs after oral gavage, the gastrointestinal non-absorption of intact SPIOs in a hydrophilic or lipophilic surrounding was measured in mice with such high sensitivity for the first time. After intravenous injection, polymer-coated, 65Zn-Qdots were mainly taken up by the liver and spleen, which was different from that of ionic 65ZnCl2. Following the label for 4 weeks, an indication of substantial degradation of the nanoparticles and the release of the label into the Zn pool was observed. Confocal microscopy of rat liver cryosections (prepared 2 h after intravenous injection of polymer-coated Qdots) revealed a colocalization with markers for Kupffer cells and liver sinusoidal endothelial cells (LSEC), but not with hepatocytes. In J774 macrophages, fluorescent Qdots were found colocalized with lysosomal markers. After 24 h, no signs of degradation could be detected. However, after 12 weeks, no fluorescent nanoparticles could be detected in the liver cryosections, which would confirm our 65Zn data showing a substantial degradation of the polymer-coated CdSe/CdS/ZnS-Qdots in the liver.
Keywords: biodistribution; chromium(III); 51Cr; quantum dots; SPIOs; zinc metabolism; 65Zn